2017
DOI: 10.1055/s-0037-1604088
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Conditioning as a Hemostatic Intervention in Surgery and Cardiac Procedures: A Systematic Review

Abstract: Ischemic conditioning induced by nonlethal cycles of tissue ischemia and reperfusion attenuates ischemia–reperfusion injury. The objective of this study is to systematically review the effects of local and remote ischemic conditioning on laboratory parameters of hemostasis and the clinical outcomes of thromboembolism or bleeding in patients undergoing surgery or cardiac procedures. PubMed and Embase were searched for relevant human trials published in English between January 1, 1986, and September 7, 2016, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 104 publications
(279 reference statements)
0
7
0
Order By: Relevance
“…RIPC attenuates platelet activation in patients undergoing heart catheterization procedures [5, 6] and long-term remote ischemic conditioning increases fibrinolysis in patients with cardiovascular disease [7] and cerebrovascular disease [8]. Correspondingly, a recent systematic review shows that remote ischemic conditioning may reduce the risk of thrombosis in patients undergoing surgery or cardiac procedures [9]. Regarding cancer surgery, RIPC has been shown to reduce the incidence of postoperative ischemic lesions in patients undergoing brain tumor resection [10].…”
Section: Introductionmentioning
confidence: 99%
“…RIPC attenuates platelet activation in patients undergoing heart catheterization procedures [5, 6] and long-term remote ischemic conditioning increases fibrinolysis in patients with cardiovascular disease [7] and cerebrovascular disease [8]. Correspondingly, a recent systematic review shows that remote ischemic conditioning may reduce the risk of thrombosis in patients undergoing surgery or cardiac procedures [9]. Regarding cancer surgery, RIPC has been shown to reduce the incidence of postoperative ischemic lesions in patients undergoing brain tumor resection [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, all flaps were viable following 7 h reperfusion evaluated by Doppler measurement and clinical observation except one flap in the control group. Four 5‐min cycles of extremity ischemia–reperfusion have been administered in most clinical trials on RIC in cardiovascular surgery and procedures (Krag & Hvas, ). Hence, three 10‐min cycles of limb ischemia–reperfusion in the present study might not be the optimal protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The review by Krag and Hvas summarizes the existing evidence of the effects of local or remote ischemic conditioning on laboratory hemostasis measures as well as the incidence of thromboembolism and bleeding in patients undergoing surgery or cardiac procedures. 16 This systematic review points to the fact that although conditioning consistently reduced platelet activation in patients undergoing cardiac procedures, the intervention did not increase bleeding risk, but notably the majority of studies also indicated that the intervention did not reduce arterial thromboembolic risk in surgery or other cardiac procedures. 16 Thus, the possible role of ischemic conditioning during surgery still needs further investigations.…”
mentioning
confidence: 90%